Selling Costs - Shone, Robert M. (Review of Economic Studies, 1935)
Journal Article Selling Costs Get access Robert M. Shone Robert M. Shone London Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 2, Issue 3, June 1935, Pages 225–231, https://doi.org/10.2307/2967589 Published: 01 June 1935